Pengaruh Kompres Dingin dan Kompres Hangat Terhadap Penurunan Nyeri Dismenore Pada Remaja Putri di Kabupaten Cirebon Tahun 2024 - Rany Muliany Sudirman; Ilda Widianingsih; Reni Fatmawati (Jurnal Keperawatan Galuh, 2025)
Dysmenorrhea is a common health problem among adolescent girls and may interfere with daily activities. Non-pharmacological management is needed as a safe and easily applicable alternative, including cold and warm compress therapy. This study aimed to analyze the effects of cold and warm compresses on reducing dysmenorrhea pain and to compare the effectiveness of both interventions among adolescent girls. This study employed a quasi-experimental design with a pretest–posttest approach. A total of 32 adolescent girls aged 15–19 years in Cikancas Village, Beber District, Cirebon Regency, were selected using accidental sampling. Participants were divided into two intervention groups: cold compress and warm compress. Pain intensity was measured before and after the interventions using a pain scale. Data were analyzed using the Friedman test. The results showed that both cold and warm compresses significantly reduced dysmenorrhea pain (p < 0.05). The reduction in pain intensity was greater in the warm compress group compared to the cold compress group. A significant difference in effectiveness was found between the two interventions, indicating that warm compress therapy was more effective in reducing dysmenorrhea pain. Both cold and warm compresses are effective in reducing dysmenorrhea pain; however, warm compress therapy is more strongly recommended as a non-pharmacological intervention in adolescent nursing practice.